Practice of face-perpendicular preconditioning for safe remnant extraction - Zvarivadza, T.; Sengani, F. (CRC Press, 2022)
Remnant mining has been considered to be a hazardous and difficult task to conduct in deep to ultra-deep gold mines in South Africa. Face-perpendicular preconditioning practice, with gradual extraction of a remnant pillar and appropriate support design were implemented in order to mine out a portion of the remnant pillar at a deep level gold mine in South Africa. Map 3D numerical modelling software was used to design the mining stopes and simulate the Energy Release Rate (ERR) when mining the remnant pillar. Micro seismic monitoring was also conducted to compare the seismicity rate along the vicinity of the remnant pillar. In this investigation, five face-perpendicular preconditioning holes were implemented at 2.5 m height stope and 4 m wide stope. The production advance was 1.5 m per blast and face perpendicular preconditioning holes were 4 m long. The results of the study indicated gradual improvement of seismic activity along the vicinity of the remnant pillar during mining, with gradual reduction in ERR. The support performance was found to be good, with no faceburst or pillar burst reported during mining. Lastly, the fracturing on the sidewall and hangingwall was found to have improved as compared to previous attempts where several falls of ground were reported.